ESTIMASI BIOMASSA DAN AKUMULASI HARA TEGAKAN JATI (TECTONA GRANDIS L.F) DI TELUK PANDAN, KUTAI TIMUR, KALIMANTAN TIMUR - Veronika Murtinah (Fakultas Kehutanan Universitas Mulawarman, 2018)
Biomass studies are important because they are closely related to other study interests. Estimation of the amount of forest stand biomass is highly relevant to the study of biogeochemical cycles. This study aims to determine the amount of biomass and macro nutrient content in teak stands. By calculating the biomass estimation and analyzing the nutrient content it will be known the amount of nutrient accumulation in biomass. The results of this study are: Total of teak stand biomass of 39,26 ton / ha, including stem component as much as 21,64 ton / ha (55%), branch + twig 11,79 ton / ha (30%), bark component 3.71 ton / ha (9%) and leaf component 2.13 ton / ha (5%). The highest N concentration of nutrients in leaf components, for the highest P in branches + twigs, whereas K, Ca and Mg were highest in the bark component. The highest accumulation of nutrient biomass is Ca (194.4 kg / ha), followed by K (189.7 kg / ha), P (92.4 kg / ha), N (53.5 kg / ha) and Mg (48.4 kg / ha).